Security lies in obedience - Voices of young women of a slum in Pakistan - Johansson Eva; Hamid Saima; Rubenson Birgitta (BMC, 2010)
Abstract Background Existing literature shows that young people, especially women, have poor knowledge about sexuality and reproductive health. Many of the difficulties young women experience are related to beliefs and expectations in society making them more vulnerable to reproductive ill health. The objective of this study was to explore how young women living in a slum in Islamabad are prepared for marriage and how they understand and perceive their transition to marriage and the start of sexual and childbearing activity. Methods Twenty qualitative interviews and three focus group discussions were conducted with young women residing in a slum of Islamabad. Content analysis was used to explore how the participants represented and explained their situation and how decisions about their marriage were made. Results The main theme identified was security lies in obedience. The two sub-themes contributing to the main theme were socialization into submissiveness and transition into adulthood in silence. The theme and the sub-themes illustrate the situation of young women in a poor setting in Pakistan. Conclusion The study demonstrates how, in a culture of silence around sexuality, young women's socialization into submissiveness lays the foundation for the lack of control over the future reproductive health that they experience.